The Relation between Some Hormonal And Biochemical Parameters In Infertile Women - A. Tayes, Amna; M. Rahim, Saleh; M. Yaseen, Enas (Tikrit Journal of Pharmaceutical Sciences, 2023)
Infertility is the most gynecological problem which is increasing all over the world.Many studies were done and many theories were tried to put the pathophysiology andcauses of infertility in order to find solutions to this problem. The aim of this study is:-1. To study the distribution of the problem all over Tikrit governorate.2. To study the relation between some hormones, biochemical parameters and infertility.Patients and Methods: 600 infertile patients were enrolled .The study conducted atobstetrics and gynecology out-patient of Tikrit Teaching Hospital. The primaryinvestigations of infertility were done to all women. Seventy two patients complained ofovarian cause infertility were taken randomly as a group -1- and 18 normal fertilewomen as a control group or group -2- to study FSH, LH, prolactin, insulin, leptin, TSH,T3, T4, blood sugar, lipid profile, BMI ,Glutathione (internal anti-oxidant) andMalondialdehyde ( oxidative stress product). Results: infertility increased in Iraq after2003 war. The primary infertility is more than secondary infertility. Many factorsassociated with it such as: age, BMI, blood groups, blood sugar, lipids profile andhormones. Different relations between study’s hormones, Glutathione andMalondialdehyde. Conclusion: The environmental factors can participates in infertilitysince 2003 in Iraq. Different hormones such as FSH,LH,Prolactin,Insulin, TSH, T4, T3,Leptin and others play a role in pathogenesis and different mechanisms of infertility.These hormones and infertility at the end result would be affected by oxidative stress ofthe body.